3D isotropic T2-weighted fast spin echo (VISTA) versus 2D T2-weighted fast spin echo in evaluation of the calcaneofibular ligament in the oblique coronal plane. Issue 2 (February 2017) - Park, H.J.; Lee, S.Y.; Choi, Y.J.; Hong, H.P.; Park, S.J.; Park, J.H.; Kim, E.
Abstract : Aim: To investigate whether the image quality of three-dimensional (3D) volume isotropic fast spin echo acquisition (VISTA) magnetic resonance imaging (MRI) of the calcaneofibular ligament (CFL) view is comparable to that of 2D fast spin echo T2-weighted images (2D T2 FSE) for the evaluation of the CFL, and whether 3D VISTA can replace 2D T2 FSE for the evaluation of CFL injuries. Materials and methods: This retrospective study included 76 patients who underwent ankle MRI with CFL views of both 2D T2 FSE MRI and 3D VISTA. The signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) of both techniques were measured. The anatomical identification score and diagnostic performances were evaluated by two readers independently. The diagnostic performances of 3D VISTA and 2D T2 FSE were analysed by sensitivity, specificity, and accuracy for diagnosing CFL injury with reference standards of surgically or clinically confirmed diagnoses. Surgical correlation was performed in 29% of the patients, and clinical examination was used in those who did not have surgery (71%). Results: The SNRs and CNRs of 3D VISTA were significantly higher than those of 2D T2 FSE. The anatomical identification scores on 3D VISTA were inferior to those on 2D T2 FSE, and the differences were statistically significant ( p <0.05). There were no significant differences in diagnostic performance between the two sequences when diagnoses were classified as normal or abnormal. Conclusion: Although the image quality of 3D VISTA MRI of the CFL view is not equal to that of 2D T2 FSE for the anatomical evaluation of CFL, 3D VISTA has a diagnostic performance comparable to that of 2D T2 FSE for the diagnosis of CFL injuries. Highlights: We compared oblique coronal view 3D VISTA images with 2D FSE in the diagnosis of calcaneofibular ligament injury. The anatomic identification scores on 3D VISTA were inferior to those on 2D T2 FSE. There were no significant differences in diagnostic performance between the two sequences.